Petrografia e litogeoquímica do minério disseminado e venular de depósitos auríferos da província de Alta Floresta (MT), cráton amazônico - Campos, Nicholas Peixoto da Silveira [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The Alta Floresta Gold Province (AFGP), northeastern of Mato Grosso State, represents a crustal segment of the southern sector of the Amazon Craton with approximately 500 km in length and WNW-ESE direction. It consists of plutono-volcanic and volcanosedimentary sequences of the Paleo-Mesoproterozoic tectonically limited to the south by Caiabis Graben, and to the north by Cachimbo Graben, which separates the AFGP from the Tapajós Auriferous Province, in the State of Pará. Primary gold mineralizations total more than a hundred small deposits, and occur concentrated between the Terra Nova do Norte, Peixoto de Azevedo, Matupá and Novo Mundo counties, aligned according to NW-SE (Peru-Trairão Alignment). In this work, three main typologies of primary gold mineralizations are subdivided, with case study of five deposits in the eastern sector of the PAAF. The group (1), disseminated deposits of Au + Cu, is given by Pé Quente and Serrinha deposits; group (2), structurally controlled Au + Cu, Paraíba and Peteca deposits; group (3), structurally controlled Au + base metals, Francisco deposit. The petrography of the mineralized zones reveals a variety of hydrothermal alterations in nature (potassic, sodic, phyllic, propylitic, sericitic, chloritic, silicification, sulfidation, carbonation) and style (pervasive, fissural, venular and combinations thereof). The lithogeochemistry allows the individualization of trends of the three groups in the behavior of major elements (e.g. Al2O3, Fe2O3), minor elements (e.g. Cu, Co, Ni) and trace elements (e.g. La, Ce). However, a strong regency of the mineralogy of hydrothermal paragenesis is observed in the concentrations of elements, particularly the major ones, which makes it difficult to identify geochemical trends of larger scales. In this way, the petrographic ... (Complete abstract electronic access below)

A Província Aurífera de Alta Floresta (PAAF), centro-norte do Estado do Mato Grosso, representa um segmento crustal do setor centro-sul do Cráton Amazônico com aproximadamente 500 km de extensão e direção WNW-ESE. Constitui-se por sequências plutono-vulcânicas e vulcano-sedimentares do Paleo- ao Mesoproterozóico limitadas tectonicamente a sul pelo Gráben dos Caiabis, e a norte pelo Gráben do Cachimbo, que separa a PAAF da Província Aurífera do Tapajós (PAT), no Estado do Pará. As mineralizações primárias de ouro totalizam mais de uma centena de depósitos de pequeno porte, e ocorrem concentradas entre os municípios de Terra Nova do Norte, Peixoto de Azevedo, Matupá e Novo Mundo, alinhados segundo NW-SE (Alinhamento Peru-Trairão). Neste trabalho, subdividemse três tipologias principais de mineralizações primárias de ouro, com estudo de caso de cinco depósitos do setor leste da PAAF. O grupo (1), depósitos disseminados de Au + Cu, é dado pelos depósitos Pé Quente e Serrinha; o grupo (2), depósitos filonares de Au + Cu, pelos depósitos Paraíba e Peteca; o grupo (3), depósito filonar de Au + metais base, corresponde ao depósito Francisco. A petrografia das zonas mineralizadas revela alterações hidrotermais diversas em natureza (potássica, sódica, fílica, propilítica, sericítica, clorítica, silicificação, sulfetação, carbonatação) e estilo (pervasivo, fissural, venular e combinações destes). A litogeoquímica permite a individualização de tendências dos três grupos no comportamento de elementos maiores (e.g. Al2O3, Fe2O3), menores (e.g. Cu, Co, Ni) e traço (e.g. La, Ce). Ressalta-se, porém, forte regência da mineralogia das paragêneses hidrotermais nas concentrações de elementos, em especial os maiores, o que dificulta... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Mineralogia; Ouro; Crátons; Petrologia; Alta Floresta (MT)